INCIDENCE OF CONTRAST-INDUCED NEPHROPATHY FOLLOWING CHRONIC TOTAL OCCLUSION PERCUTANEOUS CORONARY INTERVENTION - REHMAN , SU; HUSSAIN , SA; SHAHID , M; SULAIMAN, MR; ARBAB, MA; KHAN , S (Biological and Clinical Sciences Research Journal, 2024)
Contrast-induced nephropathy (CIN) is a potentially serious complication following percutaneous coronary intervention (PCI), particularly in patients with chronic total occlusion (CTO). It is characterized by an acute deterioration in renal function after exposure to contrast media. CIN is associated with increased morbidity, hospital stays, and long-term renal outcomes, making it crucial to identify and mitigate its incidence. This study aimed to evaluate the incidence of CIN in patients undergoing CTO-PCI and its associated complications. Objective: To assess the incidence of contrast-induced nephropathy (CIN) following percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) and evaluate in-hospital complications, hospital stay duration, and short-term mortality. Methods: This cross-sectional study was conducted with ethical approval at a tertiary care hospital, including 118 patients who underwent PCI for CTO at the Department of Cardiology, Lady Reading Hospital Peshawar, Pakistan from 10th June 2023 to 09th June 2024. Standardized pre- and post-procedural hydration protocols were implemented to reduce the risk of CIN, and non-ionic, iso-osmolar contrast agents were used. CIN was defined as a 25% increase in serum creatinine or an absolute increase of ≥0.5 mg/dL within 48–72 hours post-procedure. Data on demographic characteristics, complications, and mortality were collected and analyzed using SPSS Version 25, with categorical variables expressed as percentages and continuous variables as means. Chi-square tests were used to assess statistical significance, with P-values < 0.05 considered significant. Results: Of the 118 patients included, the mean age was 56.34 years, and 52.5% were male. Age distribution showed that 43.2% were between 51-60 years, while 33.1% were between 61-70 years. CIN was observed in 6.8% of patients, with 9.7% of males and 3.6% of females affected (P=0.188). In-hospital complications included arrhythmias in 4.2% of patients, heart failure in 0.8%, and mortality in 0.8%. Hospital stay averaged 5.94 days, with no significant differences in CIN incidence across age groups (P=0.186). Conclusion: The incidence of contrast-induced nephropathy following PCI for chronic total occlusion is a clinically significant issue, affecting 6.8% of patients despite preventative measures. This emphasizes the need for ongoing risk assessment, monitoring, and the implementation of effective prevention strategies. Further research is warranted to refine risk stratification tools and develop targeted interventions to minimize CIN incidence, particularly in high-risk patient populations.